Posterior stability in posterior-stabilized vs medially congruent total knee replacement: A radiological comparison of two polyethylene designs in a single model - Leonardo Stramazzo; Nicolo’ Bassi; Stefano Ghirardelli; Tommaso Amoroso; Leonardo Osti; Pier Francesco Indelli (Journal of Orthopaedics, Trauma and Rehabilitation)
Objective: The purpose of this radiological study was to assess the posterior laxity of a single model of a total knee arthroplasty design (TKA) having a medially constrained (MC) or a Posterior-Stabilized (PS) polyethylene insert using a well-documented stress x-ray. To the authors knowledge, this is the first report evaluating MC TKA outcomes according to the “kneeling view.” Materials and Methods: Sixty patients with non-traumatic primary knee osteoarthritis undergoing TKA were first matched by age, sex, BMI and diagnosis and then divided in two groups: group A (37 knees) received a MC TKA and group B (23 knees) a PS implant made by the same manufacturer. In all cases the posterior cruciate ligament (PCL) was resected. All patients underwent the same postoperative “kneeling view” and were also clinically evaluated according to the Knee Society Score (KSS) and Oxford Knee Score (OKS). Radiographic measurements were taken by tracing a line along the posterior cortex of the tibia and then measuring the perpendicular distance to a point marked at the posterior corner of Blumensaat’s line. Results: At 12 months minimum FU, no statistically significant differences were found between the two groups in all the clinical scores. There was a statistically significant difference on kneeling view values between the two groups (P = 0.0002): the mean value in the MC group was −1.97 ± 3.8 mm while was −5.6 ± 3.1 mm in the PS group. In both groups, the average position of the posterior cortex of the tibia was anterior to the posterior corner of Blumensaat’s line, showing absence of instability in flexion. Conclusion: This study highlighted that the PCL removal, accompanied by a precise surgical technique, did not increase the instability in flexion in two groups of patients having the same TKA design but polyethylene inserts characterized by different levels of constraint.